Efficacy of a perceptual and visual-motor skill intervention program for students with dyslexia - Fusco, Natália; Germano, Giseli Donadon; Capellini, Simone Aparecida (Sociedade Brasileira de Fonoaudiologia, 2015)
Purpose: To verify the efficacy of a perceptual and visual-motor skill intervention program for students with dyslexia. Methods: The participants were 20 students from third to fifth grade of a public elementary school in Marília, São Paulo, aged from 8 years to 11 years and 11 months, distributed into the following groups: Group I (GI; 10 students with developmental dyslexia) and Group II (GII; 10 students with good academic performance). A perceptual and visual-motor intervention program was applied, which comprised exercises for visual-motor coordination, visual discrimination, visual memory, visual-spatial relationship, shape constancy, sequential memory, visual figure-ground coordination, and visual closure. In pre- and post-testing situations, both groups were submitted to the Test of Visual-Perceptual Skills (TVPS-3), and the quality of handwriting was analyzed using the Dysgraphia Scale. Results: The analyzed statistical results showed that both groups of students had dysgraphia in pretesting situation. In visual perceptual skills, GI presented a lower performance compared to GII, as well as in the quality of writing. After undergoing the intervention program, GI increased the average of correct answers in TVPS-3 and improved the quality of handwriting. Conclusion: The developed intervention program proved appropriate for being applied to students with dyslexia, and showed positive effects because it provided improved visual perception skills and quality of writing for students with developmental dyslexia.

Objetivo : Verificar a eficácia de um programa de intervenção com habilidades percepto-viso-motoras para escolares com dislexia. Métodos: Participaram 20 escolares do terceiro ao quinto ano do Ensino Fundamental público da cidade de Marília (SP), de 8 anos a 11 anos e 11 meses de idade, sendo distribuídos nos seguintes grupos: GI (dez escolares com dislexia do desenvolvimento) e GII (dez escolares com bom desempenho acadêmico). Foi aplicado um programa de intervenção percepto-viso-motora composto de exercícios para a coordenação viso-motora, a discriminação visual, a memória visual, a relação viso-espacial, a constância de forma, a memória sequencial, a figura-fundo visual e a closura visual. Em situação de pré e pós-testagem, ambos os grupos foram submetidos à aplicação do Teste de Habilidades Perceptivas Visuais (TVPS-3), e a análise da escrita foi realizada através da Escala de Disgrafia. Resultados: Os resultados estatísticos analisados evidenciaram que ambos os grupos de escolares apresentaram disgrafia na pré-testagem. Nas habilidades de percepção visual, o GI apresentou desempenho inferior em relação ao GII, assim como na qualidade da escrita. Após ser submetido ao programa de intervenção, o GI aumentou as médias de acerto no TVPS-3 e melhorou a qualidade de escrita. Conclusão: O programa de intervenção elaborado se mostrou apropriado para ser aplicado em escolares com dislexia, assim como mostrou efeitos positivos, pois proporcionou melhora das habilidades de percepção visual e na qualidade da escrita de escolares com dislexia do desenvolvimento.
Eficácia de um programa de intervenção percepto-viso-motora para escolares com dislexia
Keywords: Rehabilitation; Visual; Perception; Dyslexia Handwriting; Reabilitação; Percepção Visual; Dislexia; Escrita manual